Colors of Jupiter's large anticyclones and the interaction of a Tropical Red Oval with the Great Red Spot in 2008. Issue 12 (23rd December 2013) - Sánchez‐Lavega, A.; Legarreta, J.; García‐Melendo, E.; Hueso, R.; Pérez‐Hoyos, S.; Gómez‐Forrellad, J. M.; Fletcher, L. N.; Orton, G. S.; Simon‐Miller, A.; Chanover, N.; Irwin, P.; Tanga, P.; et al.
Abstract [1] The nature and mechanisms producing the chromophore agents that provide color to the upper clouds and hazes of the atmospheres of the giant planets are largely unknown. In recent times, the changes in red coloration that have occurred in large‐ and medium‐scale Jovian anticyclones have been particularly interesting. In late June and early July 2008, a particularly color intense tropical red oval interacted with the Great Red Spot (GRS) leading to the destruction of the tropical red oval and cloud dispersion. We present a detailed study of the tropical vortices, usually white but sometimes red, and a characterization of their color spectral signatures and dynamics. From the spectral reflectivity in methane bands we study their vertical cloud structure compared to that of the GRS and BA. Using two spectral indices we found a near correlation between anticyclones cloud top altitudes and red color. We present detailed observations of the interaction of the red oval with the GRS and model simulations of the phenomena that allow us to constrain the relative vertical extent of the vortices. We conclude that the vertical cloud structure, vertical extent, and dynamics of Jovian anticyclones are not the causes of their coloration. We propose that the red chromophore forms when background material (a compound or particles) is entrained by the vortex, transforming into red once inside the vortex due to internal conditions, exposure to ultraviolet radiation, or to the mixing of two chemical compounds that react inside the vortex, confined by a potential vorticity ring barrier.